The North American opioid epidemic: current challenges and a call for treatment as prevention - Devesh Vashishtha; Maria Luisa Mittal; Daniel Werb (BMC, 2017)
Abstract There is a need for creative, public health-oriented solutions to the increasingly intractable problems associated with the North American opioid epidemic. This epidemic is a fundamentally continental problem, as routes of migration, drug demand, and drug exchange link the USA with Mexico and Canada. The challenges faced throughout North America include entrenched prescribing practices of opioid medications, high costs and low availability of medication-assisted treatment (MAT), and policy approaches that present substantial barriers to care. We advocate for the scale up of a low-threshold treatment model for MAT that incorporates the best practices in addiction treatment. Such a model would remove barriers to care through widespread treatment availability and affordability and also a policy of decriminalization. Given that MAT reduces the frequency of drug injecting among opioid injectors, this treatment model should also be guided by an understanding of the socially communicable nature of injection drug use, such that increasing MAT availability may also prevent the spread of injecting practices to individuals at risk of transitions from non-injection to injection drug use. To that end, the "Treatment as Prevention" model employed to respond to the individual- and population-level risks for HIV/AIDS prevention could be adapted to efforts to halt the North American opioid epidemic.